Thermodynamics of mixing in diopside-jadeite, CaMgSi2O6-NaAlSi2O6, solid solution from staticlattice energy calculations - Vinograd, V.; Gale, Julian; Winkler, B. (Springer-Verlag, 2007)
Static lattice energy calculations (SLEC), based on empirical interatomic potentials, have beenperformed for a set of 800 different structures in a 2 2 4 supercell of C2/c diopside with compositionsbetween diopside and jadeite, and with different states of order of the exchangeable Na/Ca and Mg/Al cations. Excess static energies of these structures have been cluster expanded in a basis set of 37 pair-interaction parameters. These parameters have been used to constrain Monte Carlo simulations of temperature-dependent properties in the range of 273?2,023 K and to calculate a temperature?composition phase diagram. The simulations predict the order?disorder transition in omphacite at1,150 20C in good agreement with the experimental data of Carpenter (Mineral Petrol 78:433?440, 1981). The stronger ordering of Mg/Al within the M1 site than of Ca/Na in the M2 site is attributed to the shorter M1?M1 nearest-neighbor distance, and, consequently, the stronger ordering force. The comparison of the simulated relationship between the order parameters corresponding to M1 and M2 sites with the X-ray refinement data on natural omphacites (Boffa Ballaran et al. in Am Mineral83:419?433, 1998) suggests that the cation ordering becomes kinetically ineffective at about 600C.